In the name of women? Feminist readings of policies for women's entrepreneurship in Scandinavia. Issue 1 (March 2017) - Pettersson, Katarina; Ahl, Helene; Berglund, Karin; Tillmar, Malin
Highlights: We develop a comprehensive analytical tool, building on six different feminist theoretical approaches. We find that polices give precedence to economic growth in a non-feminist way, even if a liberal feminist perspective exist. In the name of supporting women, the actual aim of policies for women entrepreneurs often seems to be economic growth. Women are seen merely as an untapped, and yet not fully adequate, resource. Abstract: Policy actors seeking to stimulate entrepreneurship sometimes give special attention to women. It is not given, however, that policy initiatives for women entrepreneurs necessarily contribute to gender equality, to social change for women – such as enhancing entrepreneurship as a means to women's well-being and financial or other independence – or to gendered change of society. We claim that the outcomes depend on the premises behind the policies. The purpose of this paper is to conduct an analysis of the feminist approaches that are taken in policies for women's entrepreneurship in the Scandinavian countries. We analyse how these policies argue for women's entrepreneurship, how they position women, and what assumptions they hold with respect to women and their businesses. We analyse and compare state-level polices that have been implemented by the national governments in three Scandinavian countries; Denmark, Norway, and Sweden, during the period 2005–2015. A comprehensive analytical tool, building on six different feminist theoretical approaches, is developed. We find that, even if a liberal feminist perspective is present, along with elements of other feminist approaches, polices give precedence to economic growth in a non-feminist fashion. Over time, economic growth becomes the key focus, while feminist approaches are silenced. We observe that, in the name of supporting women, the actual aim of policies for women entrepreneurs often seems to be economic growth, and women are seen merely as an untapped, and yet not fully adequate, resource.